Boron-conjugated pyrenes as fluorescence-based molecular probes and security markers - Wakchaure, Vivek Chandrakant; Das, Tamal; Babu, Sukumaran Santhosh (ChemPlusChem, 2019)
Boron-embedded aromatic hydrocarbons are a class of molecules known for their distinct electronic and/or optoelectronic properties and are thus suitable for many potential applications. Among those, boronic ester and acid containing molecules have been widely used for sensing and molecular recognition applications, respectively. We compared the sensing and molecular recognition properties of two boron-containing pyrene derivatives for fluoride and glucose sensing applications. The presence of four boronate ester groups enabled fluoride ion sensing at the mu M level. The boronic acid derivative is very selective towards glucose compared to other saccharides. Furthermore, we used the mechano-responsive fluorescence changes and self-assembly of these derivatives, respectively, for fluorescence-based inkless and ink (water)-based writing in invisible security labeling applications.
Keywords: boron; carbohydrates; mechanoluminescence; pyrene; sensors